A Review of Terrestrial and Canopy Malaise Traps. (5th December 2020) - Skvarla, Michael J; Larson, Jonathan L; Fisher, J Ray; Dowling, Ashley P G
Abstract: Malaise traps are important tools for the large-scale collection of arthropod taxa. Here, an extensive review of the history and literature concerning Malaise and canopy traps is given. This review highlights how trap design and placement can affect trap catch, which will help researchers to make more informed choices when planning research endeavors. Additionally, terrestrial and canopy-style Malaise traps are compared to each other and other types of arthropod traps.